Social influencer factors that affect young adult buying behaviour in Seremban / Muhammad Zarul Hisyamuddin Mohd Zaidi and Nurul Aqilah Kamaruddin - Mohd Zaidi, Muhammad Zarul Hisyamuddin; Kamaruddin, Nurul Aqilah (2022)
The purpose of the study is to examine the factors of the social influencers towards young adult buying behaviour in Seremban, Negeri Sembilan. The study was carried out in between December 2021 until January 2022. The study uses the questionnaire as their data collection method. The objective of this research is to look at the elements that influence the young adults buying behaviour towards social influencer in Malaysia in terms of source credibility, source of attractiveness and the fit between social influencer and product endorsement. To gather primary data, a sample of 388 respondents among the young adult of Seremban, Negeri Sembilan were distributed survey questionnaires. In observing the independent variables of the study (source credibility, source of attractiveness and the fit between social influencer and product endorsement) Pearson Correlation Coefficient and Multiple Linear Regression Analysis is conducted by the researcher. All of the variables have a substantial impact on the purchasing behaviour of young adults. The study concludes with a discussion of the summary findings, research implications, limitations, and recommendations for further research.